Direct radiocarbon dating and DNA analysis of the Darra-i-Kur (Afghanistan) human temporal bone. Issue 107 (June 2017) - Douka, Katerina; Slon, Viviane; Stringer, Chris; Potts, Richard; Hübner, Alexander; Meyer, Matthias; Spoor, Fred; Pääbo, Svante; Higham, Tom
Abstract: The temporal bone discovered in the 1960s from the Darra-i-Kur cave in Afghanistan is often cited as one of the very few Pleistocene human fossils from Central Asia. Here we report the first direct radiocarbon date for the specimen and the genetic analyses of DNA extracted and sequenced from two areas of the bone. The new radiocarbon determination places the find to ∼4500 cal BP (∼2500 BCE) contradicting an assumed Palaeolithic age of ∼30, 000 years, as originally suggested. The DNA retrieved from the specimen originates from a male individual who carried mitochondrial DNA of the modern human type. The petrous part yielded more endogenous ancient DNA molecules than the squamous part of the same bone. Molecular dating of the Darra-i-Kur mitochondrial DNA sequence corroborates the radiocarbon date and suggests that the specimen is younger than previously thought. Taken together, the results consolidate the fact that the human bone is not associated with the Pleistocene-age deposits of Darra-i-Kur; instead it is intrusive, possibly re-deposited from upper levels dating to much later periods (Neolithic). Despite its Holocene age, the Darra-i-Kur specimen is, so far, the first and only ancient human from Afghanistan whose DNA has been sequenced.